STUDI ANALISIS DATA DIFRAKSI SINAR-X PADA MATERIAL ZIRCON PASIR ALAM MELALUI METODE RIETVELD - Sefrilita Risqi Adikaning Rani (Universitas Islam Negeri Alauddin Makassar, 2022)
ZrSiO4 (zircon) material derived from natural sand has been successfully synthesized to produce single crystals. Structural analysis and phase change were studied by X-Ray diffraction. Rietveld analysis was carried out as a method of analyzing X-Ray Diffraction data. Zircon with a tetragonal crystal structure has been successfully synthesized to produce single crystals of ZrSiO4 with space group I41/amd. The results of the Rietveld analysis of single crystal ZrSiO4 samples with a tetragonal structure obtained lattice parameters a= 6.602727 (323) c= 5.978810 (317) with a crystal size distribution of 527.033 (0) nm and macrostrains of 0.001x10-4.